Validation of the parent version of the inventory of school attendance problems (ISAP-P) - Martin Knollmann; Volker Reissner (Frontiers in Child and Adolescent Psychiatry)
This study presents the validation of the parent version of the Inventory of School Attendance Problems (ISAP-P), which assesses a broad spectrum of symptoms associated with school attendance problems. A model with 49 items loading on 13 factors derived from the child version showed an acceptable fit (N = 296). Correlations with other measures indicated convergent and discriminant validity of the scales, but associations with the extent of school absences were not detected. Concordant scales of the child vs. parent version were correlated in the expected directions, but some scales showed low interrater agreement. Albeit these initial results support the validity of the ISAP parent version, further studies on its psychometric properties as well as on children's and parents diverging views on SAPs are needed.